Game options under Knightian uncertainty in discrete time - Bodo Rubbenstroth (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
This paper studies two player stopping games in a discrete time multiple prior framework with a finite time horizon. Optimal stopping times as well as recursive formulas for the value processes of the games are derived. These results are used to characterize the set of no-arbitrage prices for a game option. The notion of a no-arbitrage price for a game option is based on the idea to consider the payoff for fixed stopping times as an European option.
urn:nbn:de:0070-pub-29360618
Keywords: 330; Dynkin games; multiple priors; game options; incomplete Markets